GAMBARAN TINGKAT PERSEDIAAN OBAT ANTI HIPERTENSI DI APOTEK IMPHI PERIODE JANUARI – MARET 2020 - Meryta, Aries; Subagya, Guruh; Prasetya, Niko; Maulana, M Arman (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2022)
Hypertension or high blood pressure is the condition when blood pressure is at the value of 130/80 mmHg or more. This condition can be dangerous, if the patient's treatment is constrained by the quality management of a poor pharmaceutical installation (pharmacy). Efficient drug management is one of the most important factors in the success of overall management so that patients can obtain maximum treatment, and aim to avoid excess (stagnant) and deficiency (stockout) drug availability in pharmacies. The study aims to determine the degree of antihypertensive drug supply at Imphi Pharmacy from January to March 2020. This type of research uses non-experimental methods, which are types of research using quantitative descriptive methods. The sampling method uses a total sampling. The result is that all groups of antihypertensive drugs meet the average supply level of three months with a supply rate of ≥ 1.00 months, and there are two categories of drug stocks are ideal stock (supply levels ≥ 1.00 to ≤ 3.00) and stock is not ideal (inventory levels ≥ 3.00) and the most widely used antihypertensive drugs amlodipine 5 mg with an average use of 3 months as many as 1880 tablets with a stock rate of 1.22 months. All classes of antihypertensive drugs at Imphi Pharmacy each have a slowmoving drug resulting in a high level of drug supply. High levels of drug supply are influenced by several factors such as the number of declining drug requests, excess stock in the warehouse, and the transfer of the drug from generic to patent or otherwise by a physician.